2016
DOI: 10.1016/j.pt.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Myxozoa + Polypodium : A Common Route to Endoparasitism

Abstract: 0000-0001-7279-715

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Our analyses suggest that the basal divergence of the Myxo- Multigene analyses firmly place P. hydriforme as a sister taxon to the Myxozoa (present study; Chang et al, 2015). P. hydriforme uses acipenseriform fishes as hosts during larval development of a freeliving and free-reproducing adult life cycle, and it had been suggested that both, Polypodium and the Myxozoa first exploited early primitive fish and thereafter only the myxozoans adopted invertebrate hosts for the development of their adult stages (Okamura & Gruhl, 2016;Okamura et al, 2015). In contrast, the results of the present study show compelling evidence identifying invertebrates as original hosts of myxozoans before the acquisition of fish as sec- (Raikova, 1994), while in myxozoans, it infects annelids (summarized in Morris, 2010) in contrast to first stages in fish that are multicellular (El-Matbouli, Hoffmann, & Mandok, 1995;Morris & Adams, 2008).…”
Section: Independent From Exact Dates Cnidaria Originated In the Earsupporting
confidence: 55%
See 1 more Smart Citation
“…Our analyses suggest that the basal divergence of the Myxo- Multigene analyses firmly place P. hydriforme as a sister taxon to the Myxozoa (present study; Chang et al, 2015). P. hydriforme uses acipenseriform fishes as hosts during larval development of a freeliving and free-reproducing adult life cycle, and it had been suggested that both, Polypodium and the Myxozoa first exploited early primitive fish and thereafter only the myxozoans adopted invertebrate hosts for the development of their adult stages (Okamura & Gruhl, 2016;Okamura et al, 2015). In contrast, the results of the present study show compelling evidence identifying invertebrates as original hosts of myxozoans before the acquisition of fish as sec- (Raikova, 1994), while in myxozoans, it infects annelids (summarized in Morris, 2010) in contrast to first stages in fish that are multicellular (El-Matbouli, Hoffmann, & Mandok, 1995;Morris & Adams, 2008).…”
Section: Independent From Exact Dates Cnidaria Originated In the Earsupporting
confidence: 55%
“…Multigene analyses firmly place P. hydriforme as a sister taxon to the Myxozoa (present study; Chang et al., ). P. hydriforme uses acipenseriform fishes as hosts during larval development of a free‐living and free‐reproducing adult life cycle, and it had been suggested that both, Polypodium and the Myxozoa first exploited early primitive fish and thereafter only the myxozoans adopted invertebrate hosts for the development of their adult stages (Okamura & Gruhl, ; Okamura et al., ). In contrast, the results of the present study show compelling evidence identifying invertebrates as original hosts of myxozoans before the acquisition of fish as secondary/intermediate hosts: (i) Although molecular proof for sphaerosporids is still lacking, all other major clades of myxozoans are characterized by different invertebrate host groups (Bryozoa, Polychaeta and Oligochaeta; representing two to three independent host acquisition events), with invertebrate and parasite phylogenies congruent down to the most basal branches, while the history of cophylogeny of myxozoans and their fish hosts repeats itself along the time axis of each major clade indicating multiple acquisitions of fish as secondary hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Myxosporea belong to a class called Myxozoa that contains another sub-class – Malacosporea. The latter group is morphologically more complex [29]. For example, Buddenbrockia (Malacosporea) have a vermiform life cycle stage [30], appear to have myocyte cells [31] and reportedly have a life cycle stage similar to a blastula that undergoes a process similar to gastrulation [32].…”
Section: Resultsmentioning
confidence: 99%
“…The life cycle of myxozoan parasites alternates between vertebrate (mostly fish) and invertebrate (mostly annelid) hosts 9 11 . Consisting of only several cells, myxozoans are much reduced in size and tissue complexity compared to free-living cnidarians 6 , 12 . Nevertheless, myxozoans retain the phylum-defining stinging organelle, known as cnidocyst or nematocyst, but referred to historically as “polar capsule” in Myxozoa 2 , 13 – 15 .…”
Section: Introductionmentioning
confidence: 99%